Improving Accuracy of ACE-III Marking in the Wyre Forest Older Adult Community Mental Health Team - Amy Moltu; Lei-Lei Tun; Dhanjeev Marrie; Tandrila Sinha (BJPsych Open, 2025)
Aims: Accurate implementation and marking of the ACE-III (Addenbrooke’s Cognitive Examination) within memory assessments is vital in informing clinical diagnoses. The 100-mark cognitive test is subject to various nuances in its marking criteria that can easily be overlooked or misinterpreted.